Breast Specimen Measurement Methodology and Its Potential Major Impact on Tumor Size. (February 2021) - Haddad, Moreen; Xu, Bin; Pun, Cherry; Lu, Fang-I; Parra-Herran, Carlos; Nofech-Mozes, Sharon; Slodkowska, Elzbieta
Objective: Pathologic tumor size assessment highly depends on the gross specimen size once microscopic cancer size exceeds its macroscopic size, in particular if the dimension along the plane of sectioning is the greatest. We hypothesize that the method by which the specimen size is estimated can yield significantly different tumor size measurements and thus affect breast cancer staging and treatment. Methods: The size in the plane of sectioning of 50 lumpectomies over 4 cm was examined by 5 methods: measured grossly in the fresh state and postfixation, and calculated from the gross measurements by 3 different methods. For 15 mastectomies, we measured and calculated the span of the middle 4 and 6 slices using 3 methods. Results: For all 50 lumpectomies, fresh measurement yielded the largest size. The difference in size of lumpectomies was greater with increasing specimen size ( P < .001). Using the method of adding 0.4 cm per each submitted sequential section yielded the smallest size in most cases. In mastectomies the span of the middle 4 and 6 slices was significantly larger if calculated from the average slice thickness based on the specimen size. Conclusion: The method of specimen size measurement has implications in estimation of tumor size and patient management. It is essential that pathologists be aware of the technique used and its limitations. For individual slice thickness, we highly recommend using the measurements obtained at the time of grossing rather than calculating the average slice thickness from the specimen size.